The Influence Of Educational Levels And Competencies On Work Productivity (Case Study of Karangjaladri Village Office Employees, Parigi District, Pangandaran Regency) - Nurdiana, Dede; Karmila, Mila; Wibawa, Gian Riksa (Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
Productivity is the smallest ratio of income and expenditure from the results of the expenditure process that takes place during production activities. This research was conducted with the aim of finding out the influence of education level and work productivity competency in the village partially or simultaneously. Research was conducted on employees at the Karangjaladri village office. This research sample used a survey with a saturated technique. Based on the results of the F test, the level of education and competency significantly influences work productivity. The results of the T test show that the level of education and competency partially influences employee performance significantly.